Development and investigation of the flexible hydrogen sensor based on ZnO-decorated Sb2O3 nanobelts. (December 2021) - Pradeep, Natarajan; Tamil Selvi, Gopal; Venkatraman, Uma; Van Le, Quyet; Jeong, Soon Kwan; Pandiaraj, Saravanan; Alodhayb, Abdullah; Muthuramamoorthy, Muthumareeswaran; Grace, Andrews Nirmala
Abstract: Hydrogen is regarded as the next-gen fuel for vehicles to avoid the emission of toxic gases, which needs a continuous monitoring of the concentration level. In the design of the H2 sensor, especially of flexible type, a sensing layer will be blended, which affects the sensing performance of the device. Based on this concern, the present investigation is carried out to understand the effect of the bending angle toward the sensing performance of bare and ZnO (n-type)-decorated Sb2 O3 (p-type) nanobelt–based sensors for hydrogen gas. The sensing element was prepared by the thermal chemical vapor deposition followed by the drop-casting method. Furthermore, the role of the zinc precursor (molar concentration—1 M–3 M) on the preparation of ZnO-decorated Sb2 O3 nanobelts was studied. Various techniques were used to confirm the formation of ZnO-decorated nanobelts such as X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), and Fourier transform infrared spectroscopy (FTIR). From these analyses, 1 M concentration of the zinc precursor shows uniform distribution of nanoparticles over the surface of Sb2 O3 nanobelts. However, agglomeration was observed when the concentration of the zinc precursor increases from 1 M to 3 M. Later, the prepared nanobelts were deposited on the OverHead Projector (OHP) sheet by the doctor blade method for sensing hydrogen gas at 100 °C at a concentration of 1000–3000 ppm. In addition to it, the effect of the substrate bending angle (0°, 45°, 60°, and 90°) was analyzed at a fixed concentration of H2 gas (1000 ppm). From this study, it is clear that the highest sensing response was achieved for 1 M decorated nanobelts compared with bare as well as other concentrations because of uniform distribution of nanoparticles on the surface of nanobelts. Moreover, the prepared sample demonstrates better sensing performance with the bending of substrates, which suggests that the prepared sensor could be used for flexible electronic devices. The prepared nanobelts show a good H2 gas–sensing response even with bending of the substrates. The work suggests that the prepared sensor is applicable for flexible electronic devices. Graphical abstract: A schematic depicting the mechanism of hydrogen sensing using ZnO-coated Sb2 O3 nanobelts. Image 1 Highlights: The H2 -sensing performance of bare and ZnO (n-type)-decorated Sb2 O3 (p-type) nanobelts is investigated. The highest sensing response was achieved for 1 M decorated nanobelts. The developed sensor is bendable up to 60°, which is suitable for integrating with flexible electronic devices.